Harvard business review on entrepreneurship (Harvard Business School P. BostonUS, 1999)
Examines issues such as: articulating meaningful goals; attracting the correct employees; the risk factor; and, defining and executing strategies. Provides guidelines on aspects of entrepreneural activities including: writing a business plan; determining how much capital is needed; and commercializing technology.
Located in the Learning Resource Centre